The knowledge gap hypothesis in Singapore : the roles of socioeconomic status, mass media, and interpersonal discussion on public knowledge of the H1N1 flu pandemic - Ho, Shirley S. (2013)
This study applies the knowledge gap hypothesis to examine the direct and interactive influence of socioeconomic status, mass media, and interpersonal discussion on public knowledge of the H1N1 flu pandemic in Singapore. Using a nationally representative random digit-dialing telephone survey of 1,055 adult Singaporeans, results show that attention to newspapers was not associated with a widened knowledge gap about the H1N1 pandemic between the high and low socioeconomic status individuals. Conversely, attention to television news and interpersonal discussion were associated with a narrowed knowledge disparity between the high and low socioeconomic status individuals. Findings suggest that the knowledge gap hypothesis was not supported in this study. Instead, results suggest that attention to television news and interpersonal discussions were associated with a reduced knowledge gap. Household income and risk perceptions were also found to be positively associated with public knowledge about the H1N1 flu pandemic. Both theoretical and practical implications were discussed.